EARLY CHARACTER OF ISLAM IN MEDAN: Challenging the Narrative of Religious Intolerance in an Indonesian City - Azhari Akmal Tarigan; Hasan Matsum; Muhammad Syukri Albani Nasution; Jufri Naldo; Syahrial Arif Hutagalung (Journal of Contemporary Islam and Muslim Societies)
Abstract: This study explores the early development of Islam in Medan, challenging claims that the city fosters religious intolerance. Historically, Islam was introduced through peaceful, Sufistic, and adaptive means that encouraged coexistence and cultural integration. Using a qualitative, sociological approach supported by interviews with religious and community leaders and relevant literature, the research highlights Islam’s foundational values in Medan—moderation, tolerance, and inclusivity. Although contemporary religious tensions occasionally arise, often driven by political interests, they do not represent the city’s Islamic roots. The findings affirm that Medan’s interfaith relations remain largely harmonious, and portrayals of the city as intolerant misrepresent its long-standing tradition of pluralism and social harmony. Keywords: Early Islam, Religious Tolerance, Sufism, Religious Pluralism, Indonesian Islam